Interlinguale Interferenzen in deutschsprachigen Aufsätzen slowenischer DaF-Lernender – eine korpusbasierte Fehleranalyse - Kacjan, Brigita (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
Interferences in language production are referred to in the context of language acquisition as negative transfer from one language – or from the entire linguistic repertoire of a learner – into the target language. These interferences are perceived by communication partners, or in the case of the present study, by the evaluators of the written competition essays, as errors and are assessed accordingly. However, the origins of these errors are not further investigated. Although the conditions for text production were identical for all participant groups due to the competitive nature of the task (time constraints), it is postulated that the language acquisition and learning environment of grammar school students is more conducive to success than that of vocational secondary school students, who typically have had a shorter period of language acquisition or instruction. The theoretical section briefly outlines several relevant theoretical approaches. Building on this, the study is deliberately narrowed to focus on interlingual interference. The empirical section presents a case study in which non-randomly selected German-language essays written by students from grammar schools and vocational secondary schools at the end of upper secondary education – who were invited to participate in the national German language competition – are compared and analyzed. The study investigates which interlingual interferences can be identified, to what extent they occur, and whether the origin of the error (i.e., which language from the writer’s linguistic repertoire may have caused the interference) can be determined.